Ethnobotanical Study of some Tree Medicinal Plants in Marathwada, Maharashtra - S.D. Raut2, S.A. Survase1* and (Journal of Ecobiotechnology, 2011)
Ethno botanical study was carried out along with the ethnic groups in the Marathwada region of Maharashtra. In the present study, 50 plant species belonging to 30 families were included. In this assertion, the information collected from the traditional healers was used to compare with the already accessible literature on the ethnobotany of India. The conventional ethno medicinal plants were mostly used for fever, diarrhea, dysentery, skin diseases, poison bites, wounds, piles and rheumatism. The medicinal plants used by traditional users of Marathwada region are arranged alphabetically followed by botanical name, family name, local name, distribution, locality, flowering & fruiting season and parts used, and medicinal uses.